Human recombinant FSH induces chemoresistance in human breast cancer cells via HIF-1α activation. Issue 6 (2nd April 2019) - Bergandi, L; Canosa, S; Pittatore, G; Silvagno, F; Doublier, S; Gennarelli, G; Benedetto, C; Revelli, A
Abstract: Breast cancer patients under 40 years of age who are candidate to chemotherapy with alkylating drugs may undergo controlled ovarian stimulation (COS) with recombinant human follicle-stimulating hormone (rhFSH) in order to get fertility preservation by mature oocyte cryostorage. The direct effect(s) of exogenous rhFSH on the chemosensitivity of breast cancer is currently unknown. To clarify this issue, we incubated four different breast cancer cell lines with rhFSH (10 IU/L, 24 h) and then we exposed them to doxorubicin (DOX) or cyclophosphamide (CPA). The effect(s) of rhFSH on human breast cancer cells treated with DOX or CPA was measured in terms of (1) cell viability, (2) cytotoxicity, (3) multidrug resistance (MDR) genes and proteins expression and activities, and (4) hypoxia-inducible factor 1 - alpha (HIF-1α) activation. Pretreatment with rhFSH significantly increased the viability of breast cancer cells after treatment with DOX or CPA, and reduced the lactate dehydrogenase leakage and reactive oxygen species production. Moreover, after preincubation with rhFSH, the MDR proteins (Pgp, MPR1, and BCRP) expression and activity resulted upregulated and the HIF-1α pathway activated. In addition, the use of a widely used HIF-1α inhibitor, the 3-(5′-hydroxymethyl-2′-furyl)-1-benzylindazole (YC-1), prevented the rhFSH effect on the onset of MDR. Taken together, these observations suggest that a short exposure to rhFSH induces chemoresistance to DOX and CPA in human breast cancer cells via HIF-1α activation. Abstract : Our findings represent the first evidence of a direct role for the recombinant human follicle stimulating hormone in inducing chemoresistance to doxorubicin and cyclophosphamide in different human breast cancer cells via hypoxia-inducible factor 1-alpha activation.